Platinum Cyclooctadiene Complexes with Activity against Gram‐positive Bacteria. (8th July 2021) - Frei, Angelo; Ramu, Soumya; Lowe, Gabrielle J.; Dinh, Hue; Semenec, Lucie; Elliott, Alysha G.; Zuegg, Johannes; Deckers, Anke; Jung, Nicole; Bräse, Stefan; Cain, Amy K.; Blaskovich, Mark A. T.
Abstract: Antimicrobial resistance is a looming health crisis, and it is becoming increasingly clear that organic chemistry alone is not sufficient to continue to provide the world with novel and effective antibiotics. Recently there has been an increased number of reports describing promising antimicrobial properties of metal‐containing compounds. Platinum complexes are well known in the field of inorganic medicinal chemistry for their tremendous success as anticancer agents. Here we report on the promising antibacterial properties of platinum cyclooctadiene (COD) complexes. Amongst the 15 compounds studied, the simplest compounds Pt(COD)X2 (X=Cl, I, Pt1 and Pt2 ) showed excellent activity against a panel of Gram‐positive bacteria including vancomycin and methicillin resistant Staphylococcus aureus . Additionally, the lead compounds show no toxicity against mammalian cells or haemolytic properties at the highest tested concentrations, indicating that the observed activity is specific against bacteria. Finally, these compounds showed no toxicity against Galleria mellonella at the highest measured concentrations. However, preliminary efficacy studies in the same animal model found no decrease in bacterial load upon treatment with Pt1 and Pt2 . Serum exchange studies suggest that these compounds exhibit high serum binding which reduces their bioavailability in vivo, mandating alternative administration routes such as e. g. topical application. Abstract : Metalloantibiotics : Platinum complexes are mostly known for their anticancer properties, most famously in the drug cisplatin. Herein we describe the high antibacterial properties of platinum cyclooctadiene (COD) complexes. Some of these complexes display MIC values in the nanomolar range while manifesting no toxicity in vitro and in vivo .